Uso do biocarvão no tratamento de efluente de reator UASB - Sousa, Íkaro Damião Hora (2024)
The adequate treatment of sewage is essential to secure population’s health and reduce the impact of its discharge into water bodies. Consequently, research has been conducted to develop new methods that are acceptable to existing discharge standards. The adsorption technique, for example, has been seen as a promising method in removing pollutants. In this context, biochar has attracted the attention of many researchers as an alternative adsorbent material capable of removing different types of contaminants. Therefore, the present study aimed to evaluate the efficiency of using different biochars filtering sewage as a complementary treatment approach for Upflow Anaerobic Sludge Blanket (UASB) reactor effluents, in comparison with an activated carbon filtering system, commonly used in WWTPs. The experimental phase consisted of producing biochars originated from three types of agro-industrial residues (coconut shells, corn cobs and sugarcane bagasse); characterization of theses biomasses, respective biochars, and activated carbon; assembly of four adsorbent filters to filter effluent from the UASB reactor placed at the Universidade Federal de Sergipe (UFS) ETE; and, finally, physicalchemical characterization of the raw sewage, the effluent from UASB reactor, and the filtered samples. According to the results, it was observed that all biochar filters were efficient in removing apparent color and turbidity, with emphasis on the coconut shell biochar filter (62,50% and 68,54%, respectively). In the case of concentrated effluents, all biochar filters proved to be inefficient for removing Chemical Oxygen Demand (COD), while biochar filters from sugar cane bagasse and corn cobs showed prospects for COD removal with diluted effluents (40,52% and 30,39%, respectively). As for total solids, all biochar filters proved to be efficient, with emphasis on the sugar cane biochar filter (44,16%). Finally, for total suspended solids, biochar filters only proved to be efficient with diluted effluents, with emphasis on the coconut shell biochar filter (40,47%). So, it can be concluded that the use of biochars from agro-industrial residues can be a good alternative for complementary treatments in sewage treatment plants, depending on the effluent’s characteristics and physical-chemical parameters analysed. Thus, biochars produced from coconut shells, corn cobs and sugarcane bagasse can be applied for this purpose as they presented interesting results that are close to those obtained with activated carbon filters.